STRENGTHENING ZAKAH COMPLIANCE AMONG INDONESIAN MUSLIMS THROUGH THE ROLE OF INSTITUTIONAL CAPABILITIES - Razak, Syaparuddin; Nasuka, Moh.; Syahabuddin, Syahabuddin; Arsyad, Kamaruddin; Darwis, Muh. (Journal of Islamic Monetary Economics and Finance, 2024)
This study examines the mediating role of institutional capabilities in the complex interplay between zakah regulation, leadership, and entrepreneurial competencies, aiming to understand their collective impact on the augmentation of zakah compliance. To this end, a questionnaire was distributed to 833 Indonesian Muslims who actively contribute zakat to official institutions, and the data are analyzed using partial least squares structural equation modeling. The findings underscore the pivotal role of institutional capabilities as a mediator between zakah regulation, leadership, and entrepreneurial competencies, with entrepreneurial skills exerting the most notable influence on zakah compliance. Further, perceived taqwa emerges as a robust influencer of compliance, while zakah regulation demonstrates a dual impact on both compliance and institutional capabilities. Additionally, the study advocates for prioritizing the development of entrepreneurial competencies within zakah institutions, aligning regulations with institutional growth, and nurturing perceived taqwa to fortify zakah compliance on a global scale. Departing from conventional approaches, this study adopts an innovative method by evaluating the efficacy of zakat institutions through institutional capabilities, particularly focusing on entrepreneurial competencies. The introduction of institutional capabilities as a mediating factor signifies a departure from the traditional framework, providing a novel perspective on the evaluation of resource reallocation and strategic direction.